Learners as Partners in Assessing Course Learning Outcomes in an EFL University Context - Waleed Mohammed A. Ahmed (University of Science and Technology, Sana’a, Yemen, 2023)
Learners’ achievement of Course Learning Outcomes (CLOs) seems to be a common challenge in higher education worldwide, including the EFL university context in Yemen. This might be due to the disengagement of learners as partners in setting and assessing the CLOs. Limited research has been done on the engagement of learners in assessing the achievement of EFL CLOs. Thus, this study aimed to investigate the assessment of the achievement of learning outcomes of one particular course, i.e., advanced reading as perceived and achieved by EFL learners at a private university, namely University of Science and Technology, Yemen. The quantitative approach was adopted to gather data from 81 female EFL students at the university through a 5-point Likert scale checklist of the learning outcomes of the advanced reading course and students’ overall results of the course. The data were analyzed using SPSS.21. Findings revealed that the achievement of CLOs, as perceived by participants, was average, whereas their actual performance was high. The findings also revealed that there was no correlation between learners’ perceived achievement of CLOs and their actual achievement. The study may give insights into higher education institutions about the role of EFL learners in assessing the achievement of CLOs.